Effects of Root Water Uptake Efficiency on Soil Water Utilization in Wheat (Triticum aestivum L.) under Severe Drought Environments. (4th August 2014) - Kashiwagi, J.; Morito, Y.; Jitsuyama, Y.; An, P.; Inoue, T.; Inagaki, M.
Abstract Improving wheat production in drought‐prone areas is the key to meet the increasing global demand. The importance of root traits, especially, the structural traits such as root volume and rooting depth, has been well recognized to confer drought tolerance in wheat. However, generation of knowledge on root water uptake efficiency and its application in drought adaptation breeding had lagged behind. The main objective of this study was to evaluate the relevance of the root water uptake efficiency to biomass production under acute soil water deficit in six wheat genotypes. Pot experiments were conducted under polythene rainout shelters at Hokkaido University, Sapporo, Japan, in 2010 and 2011. Under drought that was measured as smaller critical fraction of transpirable soil water (FTSW), the root systems with less reduction water uptake efficiency were found to postpone the relative transpiration decline. This study also showed the existence of substantial genotypic variation on the root water uptake efficiency among the wheat genotypes. The expression of hydrophobic root morphology under drought environments, however, did not explain the results obtained on the relative root water uptake efficiency, indicating other regulative mechanisms in operation for the regulation of transverse water flow in the roots. These findings provide new understanding of drought adaptation in wheat through variations in the root water uptake efficiency.